Alternative methods to determine infectivity of Tulane virus: A surrogate for human nororvirus. (June 2015) - Xu, Shuxia; Wang, Dapeng; Yang, David; Liu, Huashan; Tian, Peng
Abstract: Culturable animal caliciviruses are widely-used as surrogates for human norovirus (HuNoV). The infectivity of a culturable virus was traditionally determined by plaque assay and/or 50% tissue culture infectious dose (TCID50 ) assay, both of which are time-consuming and labor-intensive. Molecular approaches, such as quantitative real time RT-PCR (qRT-PCR) and RT-PCR, could be used for detection of the viral genome but yet fail to determine the infectivity of a virus. In this study, we evaluated different assays for determination of infectivity of Tulane virus (TV), a surrogate for HuNoV. The infectivity of TV was measured by RNase exposure assay, RT-PCR assays, cellular-receptor-mediated capture qRT-PCR assay, receptor-mediated in situ capture qRT-PCR assay, cell-culture-mediated amplification qRT-PCR, and confirmed by TCID50 assay. RNase exposure assay was only useful for measuring TV inactivation caused by heat. Short template RT-PCR assay did not reflect inactivation status of TV. Partial reduction in viral RNA signal could be measured by long-template RT-PCR only when TV was inactivated by thermal or chlorine treatments at full-inactivation levels. Cellular-receptor-mediated capture qRT-PCR exhibited low sensitivity and specificity for the evaluation of virus infectivity. The in situ capture qRT-PCR assay could be used to evaluate virus inactivation deriving from damage to viral capsid caused by heat and chlorine. The cell-culture-mediated amplification qRT-PCR could be used as an alternative method to rapidly determine the infectivity of TV. Highlights: Various methods have been explored to replace tissue cultured assays for Tulane virus. RNase exposure and regular RT-PCR had limited value for infectivity measurement. Cellular receptor mediated capture-qRT-PCR exhibited low sensitivity and specificity. ISC-qRT-PCR could evaluate virus inactivation deriving from damage to viral capsid. CMA-qRT-PCR has high sensitivity for infectivity measurement with less time/labor.